2013
DOI: 10.1039/c2cc37092a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient SO2capture through tuning the interaction between anion-functionalized ionic liquids and SO2

Abstract: A strategy to improve SO(2) capture through tuning the electronegativity of the interaction site in ILs has been presented. Two types of imidazolium ionic liquids that include less electronegative sulfur or carbon sites were used for the capture of SO(2), which exhibit extremely highly available capacity, rapid absorption rate and excellent reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 37 publications
1
116
1
Order By: Relevance
“…This kind of thermal behavior is similar to those of imidazolium ethyl sulfate ILs reported in the literature. 40 Meanwhile, the weight loss of 10.0% at 250°C which similarly represent the complete decomposition of ethyl sulfate …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This kind of thermal behavior is similar to those of imidazolium ethyl sulfate ILs reported in the literature. 40 Meanwhile, the weight loss of 10.0% at 250°C which similarly represent the complete decomposition of ethyl sulfate …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 These interaction energies as well as the current results (Figure 4). 8 Interaction energies between cluster model and SO 2 are listed in Table 3.…”
Section: So 2 Absorption For Monomer Modelmentioning
confidence: 99%
“…after the SO 2 absorption. It was found that the calculated absorption enthalpies of SO 2 for [SCN] and [C(CN) 3 ] based ILs are -17.4 kcal/mol and -7.7 kcal/mol 8. This longer distance in abs-com-c means a reduced interaction between ChCl and glycerol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more Electronic supplementary material The online version of this article (doi:10.1007/s00894-015-2747-5) contains supplementary material, which is available to authorized users. and more researchers have reported the use of ILs to reversibly capture SO 2 and CO 2 by utilizing both physical and chemical interactions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Very recently, Yang and Han et al [26] reported that two functionalized ILs, 1-(2-diethylaminoethyl)-3-methylimidazoliu bis (trifluoromethylsulfonyl)-imide ( A specific intermolecular interaction involving pnicogen, chalcogen and halogen atoms as acceptors of electron density, has been studied extensively in recent years [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 97%